1995
DOI: 10.1016/0006-8993(95)01006-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting enhancement of synaptic excitability of CA1/subiculum neurons of the rat ventral hippocampus by vasopressin and vasopressin(4–8)

Abstract: Vasopressin (VP) is axonally distributed in many brain structures, including the ventral hippocampus. Picogram quantities of VP injected into the hippocampus improve the passive avoidance response of rats, presumably by enhancing memory processes. Vasopressin is metabolized by the brain tissue into shorter peptides, such as [pGlu4,Cyt~']VP(4-9) and [pGlu4,Cyt~']VP(4-8), which preserve the behavioral activity but lose the peripheral activities of the parent hormone. Using brain slices, we investigated whether V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…Cognitive enhancers facilitate processes of learning and memory, and may do so by boosting attention and memory consolidation (Tuboly and Vécsei, 2013). Drugs, such as amphetamine and methylphenidate, exercise, sleep, certain foods and hormones enhance cognitive performance (Chen et al, 2011), (Chepkova et al, 1995; Ramanathan et al, 2012) (for review see Tuboly and Vécsei, 2013). Estradiol shares several intracellular pathways with cognitive processes, such as mitogen-activated protein kinase (MAPK) and phosphatidylinositol-3 kinase /protein kinase B (P13K/Akt) (D’Astous et al, 2006; Chan and Ye, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive enhancers facilitate processes of learning and memory, and may do so by boosting attention and memory consolidation (Tuboly and Vécsei, 2013). Drugs, such as amphetamine and methylphenidate, exercise, sleep, certain foods and hormones enhance cognitive performance (Chen et al, 2011), (Chepkova et al, 1995; Ramanathan et al, 2012) (for review see Tuboly and Vécsei, 2013). Estradiol shares several intracellular pathways with cognitive processes, such as mitogen-activated protein kinase (MAPK) and phosphatidylinositol-3 kinase /protein kinase B (P13K/Akt) (D’Astous et al, 2006; Chan and Ye, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It can therefore be postulated that OT fibers are present at puberty and then disappear or that it is AVP that physiologically mediates these effects. It is known that AVP plays a role in the hippocampal activity-dependent plasticity mediated by V1aRs and V1bRs (89,(96)(97)(98)(99), and the use of high concentrations of agonists and antagonists in the above-mentioned studies does not rule out the possibility of overlapping V1aR/V1bR-mediated effects. Further studies are required to assess if OT has a direct effect on the activity-dependent synaptic plasticity involved in LTP and/or long-term depression (the neurobiological substrates of memory), or if it participates in learning and memory processes by acting on other neurotransmitters/neuromodulators.…”
Section: The Neurochemical Substrates Of Ot-induced Effects On Learnimentioning
confidence: 99%
“…In line with our results, previous work has also shown that AVP excites hippocampal pyramidal neurons (Mizuno et al, 1984; Muhlethaler et al, 1982; Tiberiis et al, 1983a). Furthermore, AVP has been shown to increase LTP in CA1 region (Chepkova et al, 1995; Chepkova et al, 2001; Rong et al, 1993) and the dentate gyrus (Chen et al, 1993; Dubrovsky et al, 2003). AVP-mediated direct excitation of CA1 pyramidal neurons and indirect augmentation of glutamatergic transmission onto CA1 pyramidal neurons likely contribute to AVP-induced enhancement of learning and memory (Alescio-Lautier et al, 2000; Alescio-Lautier and Soumireu-Mourat, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the hippocampus also expresses high-density of vasopressin receptors (Audigier and Barberis, 1985; Brinton et al, 1984; Costantini and Pearlmutter, 1984; De Kloet et al, 1985). Consistent with the distribution of vasopressin and vasopressin receptors in the hippocampus, application of vasopressin enhances synaptic transmission and induces long-term potentiation (LTP) in CA1 region (Chepkova et al, 1995; Chepkova et al, 2001; Rong et al, 1993) and the dentate gyrus (Chen et al, 1993; Dubrovsky et al, 2003). Whereas vasopressin has been shown to excite hippocampal pyramidal neurons (Mizuno et al, 1984; Muhlethaler et al, 1982; Tiberiis et al, 1983a), recordings of the field potentials demonstrate that the pyramidal discharge is inhibited by vasopressin (Albeck and Smock, 1988) suggesting that vasopressin also excites non-pyramidal inhibitory interneurons to exert indirect inhibitory effects on pyramidal neurons (Muhlethaler et al, 1984).…”
Section: Introductionmentioning
confidence: 86%